Neotropical Fanniidae (Insecta, Diptera): new species of Fannia from Colombia - Grisales, Diana; Wolff, Marta; de Carvalho, Claudio J. B. (Zootaxa, 2012)
Fannia Robineau-Desvoidy is distributed in all biogeographic regions and has about 300 species. Only seven species of Fannia are recorded from Colombia. A total of 13 new species are herein described: F. chibcha sp. nov. (Cundinamarca, Mosquera), F. chingaza sp. nov. (Cundinamarca, Parque Nacional Natural- P.N.N. Chingaza), F. dorsomaculata sp. nov. (Antioquia, Amalfi), F. embera sp. nov. (Chocó, Jobí), F. iguaque sp. nov. (Cundinamarca, P.N.N. Chingaza), F. katios sp. nov. (Chocó, P.N.N. Los Katíos), F. lamosca sp. nov. (Antioquia, San Vicente), F. magdalena sp. nov. (Antioquia, Puerto Berrio), F. pijao sp. nov. (Caldas, Manizales), F. porce sp. nov. (Antioquia, Amalfi), F. quimbaya sp. nov. (Risaralda, Santuario de Flora y Fauna—S.F.F. Otún-Quimbaya), F. sumapaz sp. nov. (Cundinamarca, P.N.N. Sumapaz) and F. sutagao sp. nov. (Meta, P.N.N. Sumapaz). The majority of these species are from preserved ecosystems: forests and high mountains. The new species possibly belong to species groups of Fannia new for Colombia such as hirticeps, benjamini, grandis and anthracina. Three new records of species for Colombia, F. grandis Malloch, F. pusio (Wiedemann) and F. trimaculata (Stein), are given. An identification key to males and diagnoses and descriptions of the genus Fannia and of the species are also provided. In the addendum, photographs and illustrations of the male and female terminalia are presented.